Kesiapan Guru IPA dalam Mengimplementasikan Kurikulum Merdeka Belajar di SMP Negeri 4 Tondano : Penelitian - Dita Rohana Sitinjak; Jovialine A. Rungkat; Fransiska Harahap (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study was to determine the level of readiness of science teachers in implementing the Merdeka Belajar Curriculum at SMP Negeri 4 Tondano. The study used a qualitative descriptive research approach. The subjects of the study were 5 science teachers in grades 7, 8, and 9 at SMP Negeri 4 Tondano. Data collection techniques used observation, interviews, and questionnaires. Indicators of teacher readiness in implementing the curriculum include understanding the curriculum structure, readiness of learning plans, implementation of learning, assessment of learning, and availability of facilities and infrastructure. Data processing techniques used a Likert scale, collecting and calculating average scores, and converting scores into percentages. The results of the study showed that:1) Teachers' understanding of the curriculum structure is good, 2) readiness of learning planning is good, 3) readiness of learning implementation is good, 4) readiness of learning assessment is good, and 5) readiness of facilities and infrastructure is good. The conclusion of this study is that the readiness of science teachers in implementing the Merdeka Belajar Curriculum at SMP Negeri 4 Tondano is classified as good.